2017
DOI: 10.1080/1478422x.2017.1297601
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behaviour of Fe–40 at.-% Al intermetallics with Li or Cu additions at high temperature

Abstract: Fe-40 at.-% Al intermetallics with the addition of Li (1 and 3 at.-%) and Cu (3 and 5 at.-%) were produced using standard casting techniques. The oxidation behaviour was obtained using thermogravimetric analyses in an atmosphere of 99.99% oxygen at 800, 900, 1000, and 1100°C. The oxidation product layers on the top and cross-sectional views were characterised using SEM and energy-dispersive X-ray spectroscopy mapping. The different alumina phases can produce a double layer with different mechanical and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Although these materials have excellent behavior in high temperature conditions, they could be adequate in aqueous condition applications because of the high corrosion resistance as the effect of passive layer formation. This growing of passive layer has been presented by the Fe-Al base intermetallics exposed in O 2 gas at temperature up to 1000 °C (9,10), and in SO 2 gas at temperatures from 650 to 750 °C (11,12) inclusive. In other hand, recent corrosion studies of the iron aluminides in aqueous solution with sulfur contents have showed good corrosion resistance (13), and could be considered for potential applications in the area of energy transformation.…”
Section: Introductionmentioning
confidence: 90%
“…Although these materials have excellent behavior in high temperature conditions, they could be adequate in aqueous condition applications because of the high corrosion resistance as the effect of passive layer formation. This growing of passive layer has been presented by the Fe-Al base intermetallics exposed in O 2 gas at temperature up to 1000 °C (9,10), and in SO 2 gas at temperatures from 650 to 750 °C (11,12) inclusive. In other hand, recent corrosion studies of the iron aluminides in aqueous solution with sulfur contents have showed good corrosion resistance (13), and could be considered for potential applications in the area of energy transformation.…”
Section: Introductionmentioning
confidence: 90%